Cathinone Use Disorder in the Context of Slam Practice: New Pharmacological and Clinical Challenges - Schreck, Benoit; Guerlais, Marylène; Laforgue, Edouard; Bichon, Célia; Grall-Bronnec, Marie; Victorri-Vigneau, Caroline (Frontiers in Psychiatry, 2020)
Background: “Slam” has emerged since 2008 as a new international phenomenon among men who have sex with men (MSM); it consists of the intravenous injection of drugs before or during planned sexual activity. The practice of slam is associated with the use of psychostimulants, including synthetic cathinones. Methods: All spontaneous notifications (Nots) of slam practice reported between January 2012 and October 2019 at the Nantes addictovigilance center in France were collected and analyzed. The purpose of this work was to analyze cases of slam to characterize cathinone use disorder according to the diagnostic criteria of the DSM-5 and to further our knowledge of slam practice based on data on drug use, risk taking and harmful consequences. Results: We collected 39 slam notifications. The severity of cathinone use disorder was mild, moderate and severe for 18%, 12% and 58% of the patients, respectively. “Much time spent using cathinone” was the diagnostic criterion most often cited (82%). Conclusions: To the best of our knowledge, our study is the first to evaluate the presence of a cathinone use disorder. Cathinone use disorder seems particularly important in this population of users, and negative consequences of slam practice appear quickly.